HUBUNGAN PATRON-CLIENT DAN RITUAL PETIK LAUT - Studi Kasus Masyarakat Desa Tanjung Luar, Kabupaten Lombok Timur, Nusa Tenggara Barat - Rahmi, Nurbayu Sutiya (Sabda: Jurnal Kajian Kebudayaan, 2012)
Tanjung Luar village, located in East Lombok regency, is around 222 km2 and has good potential fishery. Continual exploitation at Tanjung Luar village with using of inefficient fishing capture would decrease the existing resource abundance. Patron-client in Tanjung Luar village society forms a community group called â€œKelompok Masyarakat Pengelola Lautâ€ that manages the fishery resource. Tradition existence â€œPetik lautâ€ also can help the fishery resource management at Tanjung Luar village, East Lombok Regency.